PENGARUH LITERASI DIGITAL, KREATIVITAS GURU DAN KOLABORASI PEMBELAJARAN TERHADAP KINERJA GURU DI PESANTREN KECAMATAN GUNUNG SINDUR KABUPATEN BOGOR - Veranita Rizal; Ersam Mahendrawan; Surasni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the suboptimal performance of teachers in Islamic boarding schools in Gunung Sindur District, Bogor Regency, as indicated by a preliminary survey with indicator achievements below 50% (30.0%–41.1%). This problem is suspected to be triggered by limited digital literacy, monotonous teaching approaches, and a minimal culture of collaboration due to the dense workload of 24-hour student care. This study aims to analyze the influence of digital literacy (X_1), teacher creativity (X_2), and learning collaboration (X_3) partially and simultaneously on teacher performance (Y). The method used is quantitative associative causal. From a population of 160 high school/Islamic high school teachers in 7 Islamic boarding schools, a representative sample of 114 respondents was taken using the Slovin formula and proportional random sampling technique. Primary data were collected through a valid and reliable 5-point Likert scale questionnaire, then analyzed using multiple linear regression. The results showed that partially, digital literacy, teacher creativity, and learning collaboration each had a positive and significant effect on teacher performance. Simultaneously (F-test), the three independent variables were shown to have a significant effect on teacher performance. The coefficient of determination (R2) of 0.651 indicates that the combined contribution of these three variables in explaining variation in teacher performance is 65.1%, while the remaining 34.9% is influenced by factors outside the model. The study's conclusions confirm that improving the performance of Islamic boarding school teachers requires comprehensive integration of technological capacity, teaching creativity, and a collaborative work ecosystem. Practical recommendations are aimed at Islamic boarding school administrators to facilitate regular ICT training, provide space for innovative teaching methods, and strengthen learning communities to reduce teacher isolation.